Knowledge, compliance, and factors influence the compliance of universal precautions among nurses - Viniththira, V.; Sivapalan, K. (University of Jaffna, 2012)
Universal Precaution (UP) is a set of guidelines which aims to protect health care workers from infections. Compliance to the UP is often minimal in low income countries, in spite of greater risk of infection. A cross sectional study was conducted to study the knowledge and compliance of UP and factors that influence the compliance among the nurses in the medical wards, Jaffna Teaching Hospital by a self administrated questionnaire. The first part assessed the knowledge, marked out of 100%. The degree of compliance was assessed through the second part and marked out of 100%. The third part inquired about the factors that influence the compliance. The data were analyzed by chi squared test. The mean for knowledge was 71.8% (SD±14.3), mean for males and females were 67% (SD±13.5) and 74.8% (SD±14.1) (p=0.24) respectively, mean of 20-30 year age group was 73.3%, 31-40 years was 74.6% and mean for older age group 41-50 and 51-60 were 65.6% and 66.8% respectively (p=0.72). Working experience did not show statistically significant relationship (p=0.259). The mean for compliance was 74.1% (SD±14.9). Age (p=0.987), sex (p=0.921), and working experience (p=0.990) did not show statistically significant relationship. In this study 57% of Nurses had needle recapping habit, which is considered as an important factor that predisposes nurses for hospital infection. Regarding factors influencing the compliance of UP, fear of being infected influenced positively and poor material availability (67%), excessive work load (59%), psychological effect on the patient especially in using mask (45%), and emergency situations (40%) negatively influence the compliance of UP. To protect the health care workers and as well as the patients, 100% compliance is necessary. This study has identified that knowledge and compliance of nurses in the medical wards of the Teaching Hospital, Jaffna is not up to expected levels. Some factors that may be responsible for this also are identified. There is a need to review the nursing curriculum with greater emphasis on UP. In-service training programs for nursing staff on UP is also recommended as indicated by some respondents in the open comment.
Keywords: Universal precautions; Compliance